KOMPARASI KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 X KOTO KABUPATEN TANAH DATAR (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The purpose of this research was to describe the following things. First, to describe the writing skills of observation report texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. Second, to describe the writing skills of expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. Third, to analyze the comparison between the writing skills of observation report texts and expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. This research is a quantitative research with descriptive analysis. Based on the research findings, the following three things were concluded. First, the writing skills of observation report texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency, were in a good qualification (76.43). Second, the writing skills of expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency, were in more than sufficient qualification (74.07). Third, there was a significant difference between the writing skills of observation report texts and expository texts of grade X SMA Negeri 1 X Koto, Tanah Datar Regency. Based on the hypothesis test conducted, it can be concluded that H1 is accepted because the tvalue is greater than the ttable. Therefore, there is a significant difference between the two texts.